Canine monocytic ehrlichiosis in Buenos Aires, Argentina: comparison of serological and molecular assays - Martín, Paula Lorena (2019)
Canine monocytic ehrlichiosis (CME) is an infectious disease caused by the bacterium Ehrlichia canis and transmitted by Rhipicephalus sanguineus sensu lato, a tick with worldwide distribution. When not diagnosed and treated early, disease can be severe. Currently, the disease is confirmed by serological or molecular assays. The objective of this study was to compare a serological assay based on immunochromatography (SPEED® EHRLI immunochromatographic test; BVT, France) and a molecular assay (a screening PCR followed by a nested PCR specific for E. canis) for the diagnosis of E. canis in suspected dogs from Buenos Aires city and southern Greater Buenos Aires, Argentina. Blood samples from 20 clinically healthy dogs (Control Group) and from 80 sick dogs suspected of having CME (Groups 1 to 4) were tested in parallel. Neither the immunochromatographic test nor the PCR assay was able to detect the presence of E. canis in the Control Group. In the group which had been previously tested by serology, the agreement between the tests was low (kappa: 0.200), whereas in the group which had been previously tested by PCR, the concordance between the tests was adequate (kappa: 0.650). The concordance between the tests evaluated in the total population studied was moderate (kappa: 0.496). The results of our study suggest that the use of rapid serological tests as a first approach, together with subsequent confirmation by PCR, will improve the diagnosis of CME.